2007
DOI: 10.1002/elan.200603737
|View full text |Cite
|
Sign up to set email alerts
|

A Suggestion of Electrochemical Biosensor for Study of Platinum(II)‐DNA Interactions

Abstract: As a consequence of the employment of platinum based cytostatic drugs in tumor diseases treatment, it became necessary not only to detect them in biological samples but also to determine and study the Pt-DNA adducts, which is highly important during investigation of resistance on antitumor treatment. Thus, the main objective of this work was to study the interactions between DNA and cisplatin. Primarily, we studied changes in electrochemical behavior of cisplatin in the presence of different concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…4C). In addition the limit quantification of apoMT was 100 pM at t A 500 s. Moreover, apoMT has been successfully used for suggestion of EDTA MT biosensor for determination of heavy metals [65]. We found out that the suggested biosensor had similar behavior as MT and/or PC biosensor, whereas the biological part of EDTA MT biosensor enabled to reach lower detection limits about 10 -30% [34,55].…”
Section: Electroanalytical Determination Of Apomtmentioning
confidence: 95%
See 1 more Smart Citation
“…4C). In addition the limit quantification of apoMT was 100 pM at t A 500 s. Moreover, apoMT has been successfully used for suggestion of EDTA MT biosensor for determination of heavy metals [65]. We found out that the suggested biosensor had similar behavior as MT and/or PC biosensor, whereas the biological part of EDTA MT biosensor enabled to reach lower detection limits about 10 -30% [34,55].…”
Section: Electroanalytical Determination Of Apomtmentioning
confidence: 95%
“…It follows from the results obtained that EDTA can really unbound metal ions from MT, which means that apoMT is presented in this solution. This procedure could be an useful alternative tool for simple, rapid and undemanding preparation of apoMT to different purposes such as a suggestion of heavy metal biosensor [65].…”
Section: Influence Of Edta On Adts Dpv Signals Of Rabbit Liver Metallmentioning
confidence: 99%
“…The labelling of signals is based on a number of papers published, which have been devoted to determination of thiols by the Brdicka reaction [16,17,39,[52][53][54][55][56][57][58][59][60][61][62][63] to structure of GSH -formation of RS2Co complex ( Figure 5B). The electrochemical behaviour of metallothionein measured by adsorptive transfer stripping technique in connection with different electrochemical methods is known [65][66][67][68][69], but the behaviour of such a small peptide as glutathione is not clear yet. As shown in Figure 5A and described by Vacek et al [15], GSH can be adsorbed on the surface of HMDE, and the modified electrode is placed in an electrochemical cell, where electrochemical analysis proceeds.…”
Section: Electrochemical Detection Of Glutathione -Use Of the Brdickamentioning
confidence: 99%
“…Metallothioneins (MT) as a metal-binding proteins represent other promising tumour markers, which are intensely studied in connection with prostate carcinoma among other diseases (29)(30)(31). It has been recently demonstrated that metallothioneins play an important role in the development and progression of some tumour diseases (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%